Digital Literacy Skills and E-Learning Success: Assessing Preparedness in Higher Education - Md. Ashfaq Rahman; Sharmin Akter; Tanvir Hossain (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study assesses the relationship between digital literacy skills and student success in e-learning environments, focusing on higher education institutions in Bangladesh. Through surveys and analysis of performance data, the research examines students' proficiency with digital tools, self-regulation, and information management skills. Findings suggest that digital literacy is crucial for adapting to e-learning formats and achieving academic success, highlighting the need for digital skills training as part of college curricula.